Causes of inflation in the Iranian economy, 1972-1990 - Tavakkoli, Ahmad (1996)
Inflation has been the focus of numerous investigations in recent decades, both for developed and developing countries. Although there is a general understanding about the consequences of inflation, its causes and cure are still controversial issues among economists. None of the two competitive views concerned with developing countries , Monetarism and Structuralism, provides a wholly successful theoretical model to explain price behaviour. This thesis attempts to suggest a synthesis for more appropriate modeling.